Regional Welfare Disparities in the Kyrgyz Republic - Atamanov, Aziz (World Bank, Washington, DC, 2013)
Kyrgyz Republic is an interesting case to study welfare disparities because of pronounced and long existed differences across various regions, rural, and urban areas of the country in spite of economic growth and overall poverty reduction (World Bank 2011). For instance urban poverty stood at 31 percent versus 40 percent in rural areas in 2011 (national statistical committee). The welfare disparities are particularly striking between the growing capital Bishkek and the other regions. Thus, for example, the poverty in the Naryn region is 50 percent versus 18 percent in the capital. The main goal of this paper is to analyze regional disparities in the Kyrgyz Republic by quantifying and separating the gap in welfare disparities in 2011 into two parts: the first part associated with observable characteristics of households and the second part associated with differences in marginal returns to these characteristics (potentially related to geographic factors). Welfare disparities are analyzed between and within the regions. In addition, the role of returns and characteristics in explaining welfare disparities both at the mean and across the distribution using oaxaca-blinder decomposition and its extensions is quantified. The proposed research is an important source of empirical evidence testing the propositions from the new economic geography. This is also the first empirical paper aimed at explaining regional welfare disparities in a country from the Central Asian region where the urban rural gap is an important component of inequality. The paper is structured as follows: it starts from the background information describing welfare disparities, economic growth and structural differences across different areas. The third section briefly discusses the methodology. The results of the decomposition are presented and discussed in the fourth section. The fifth section concludes.